2009
DOI: 10.1002/jat.1480
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of aging influence on renal toxicity caused by segment‐specific nephrotoxicants of the proximal tubule in rat†

Abstract: Little is known concerning the sensitivity of aged rats to xenobiotics inducing kidney damage. To increase this knowledge, the age-dependent response of the kidney to hexachloro-1 : 3-butadiene (HCBD) or potassium dichromate (chromate) was investigated. Rats were treated at different ages with a single dose of segment-specific nephrotoxicants of the proximal tubule, chosen on the basis of their specificity for S(3) and for S(1)-S(2) segments, respectively. The toxicological impact of these xenobiotics has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Structurally, the PT can be divided into three segments (S1, S2, and S3), with the former two segments are grouped as the proximal convoluted tubule and located in the renal cortex while the S3 proximal straight tubule is located in the outer medulla. Although recent studies showed that there are important axial differences in the function of the three segments of the PT [8], the precise role of each PT segment in the pathogenesis of AKI remains unclear [4,[9][10][11]. As such, we will focus the following discussion on the pathogenic role of PT as a whole in AKI without specifying which segment as the dominant site of injury under different circumstances.…”
Section: Histological and Physiological Basis To Target The Proximal ...mentioning
confidence: 99%
“…Structurally, the PT can be divided into three segments (S1, S2, and S3), with the former two segments are grouped as the proximal convoluted tubule and located in the renal cortex while the S3 proximal straight tubule is located in the outer medulla. Although recent studies showed that there are important axial differences in the function of the three segments of the PT [8], the precise role of each PT segment in the pathogenesis of AKI remains unclear [4,[9][10][11]. As such, we will focus the following discussion on the pathogenic role of PT as a whole in AKI without specifying which segment as the dominant site of injury under different circumstances.…”
Section: Histological and Physiological Basis To Target The Proximal ...mentioning
confidence: 99%
“…After a single injection of HCBD at 100 mg kg −1 b.w, the incidence and severity of the degenerative changes affecting the S3 segment did not appear to be influenced by age, as previously described (Zanetti et al ., ). In contrast, HD accumulation in the S1/S2 segments occurred with an age‐related incidence and severity.…”
Section: Discussionmentioning
confidence: 97%
“…GS is a very sensitive marker of kidney injury and ATPase plays an important role in material transport, energy transformation and message passing. 34,35 In this study, GS and ATPase were measured to reect the level of cell function. The GS and ATPase levels of cells in SSG were signicantly decreased (similar with PCG) by 78% and 25%, respectively, when compared with those in BG.…”
Section: Biochemical Assaysmentioning
confidence: 99%